Encyclopedia of Electrochemistry 2007
DOI: 10.1002/9783527610426.bard100107
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Oxide Electrodes

Abstract: The sections in this article are Introduction Electrode Preparation General: Transparent Conducting Oxide Films Cleaning of Substrate Surfaces Cleaning with Solvents Cleaning by Heating and Irradiation Cleaning by Stripping Lacquer Coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 611 publications
0
10
0
Order By: Relevance
“…Such reactions involve silanes, 31−33 phosphonic acids, 34 or other small molecules. 24,30 There are evidences, for instance, that indium tin oxide (ITO) modified surface increases electron transfer properties, 35 optimizes light trapping, 36,37 allows tuning surface roughness and tribological properties via any plasma activation. 38,39 However, there are still unsolved problems mainly related to long-term and thermal stability, reproducibility of the treatment, chemical surface homogeneity after modification, and controlled protocols for monolayer formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such reactions involve silanes, 31−33 phosphonic acids, 34 or other small molecules. 24,30 There are evidences, for instance, that indium tin oxide (ITO) modified surface increases electron transfer properties, 35 optimizes light trapping, 36,37 allows tuning surface roughness and tribological properties via any plasma activation. 38,39 However, there are still unsolved problems mainly related to long-term and thermal stability, reproducibility of the treatment, chemical surface homogeneity after modification, and controlled protocols for monolayer formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4a,8b To the best of our knowledge, none have studied stability of the chemically modified surfaces with acid chlorides in detail. 5 In this work, the degradation processes of the chemically modified as well as oxidized ITO surfaces with UV ozone (ITO(uv)) were studied by measuring the time change in or water contact angle (CA) after exposure of freshly prepared samples to various environments. In particular, we focused our attention on the effect of water in the environments.…”
Section: 11mentioning
confidence: 99%
“…[4][5][6] Therefore, changing the work function () of these oxide electrodes has been attempted by surface treatment with adsorption of acids and bases, 7 self-assembled monolayer (SAM) formation with polar adsorbate molecules, 8 and exposure to O 2 plasma 9 or UV ozone. 10 Among them, we have demonstrated tuning by chemical modification of ITO surfaces with various acid chloride (i.e., -SO 2 Cl, -COCl, and -PO 2 Cl 2 ) binding groups of para-substituted benzene derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indium-tin-oxide (ITO) is the most widely used as a transparent anode in organic PV cells due to its high conductivity, work function, and transparency in the visible spectral range [6]. Thus, various surface treatments of ITO have been attempted to change the work function of ITO in order to improve the properties of ITO substrates and control the charge injection barrier height reviewed in previous reports [20,21]. Although a number of groups have shown that chemical modification of ITO can be used to optimize the performance of organic lightemitting diodes (OLEDs) [20,21], there have been limited attempts to use chemical modification or chemically selfassembled monolayers (SAMs) in organic PV cells [22,23].…”
Section: Introductionmentioning
confidence: 99%